2006
DOI: 10.4315/0362-028x-69.6.1412
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Perceptions and Behaviors of Kentucky Consumers

Abstract: In several areas, Kentuckians practice more risky health behaviors than most of the rest of the nation. The Health Belief Model states that individuals with lower perceived risks practice less healthy behaviors. This study sought to determine if this was true for food safety by assessing food safety perceptions and behaviors of Kentucky consumers. Data were collected through a telephone questionnaire based on a survey by the U.S. Food and Drug Administration; 728 respondents participated. Food safety perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 17 publications
2
58
1
Order By: Relevance
“…Only 3.2% of participants of this study reported consuming hamburgers with pink inside, compared with 19% of consumers with advanced degrees (i.e., beyond a bachelor's degree) who consumed undercooked hamburgers (18). Because less than 10% of respondents in the present study held at least a bachelor's degree, results of this study seem to be consistent with those of other research projects.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Only 3.2% of participants of this study reported consuming hamburgers with pink inside, compared with 19% of consumers with advanced degrees (i.e., beyond a bachelor's degree) who consumed undercooked hamburgers (18). Because less than 10% of respondents in the present study held at least a bachelor's degree, results of this study seem to be consistent with those of other research projects.…”
Section: Discussionsupporting
confidence: 86%
“…Previous consumer food safety studies have revealed that few consumers with low household incomes have food thermometers (18), store prepared food items in the refrigerator (18), and wash cutting boards after using them for potentially hazardous food items (21). In contrast, low-income consumers are less likely to consume high-risk foods such as raw shellfish and undercooked hamburgers (21).…”
mentioning
confidence: 99%
“…23 Risk perception is thought to greatly influence personal decisions and behaviors. 15,24,25 Our study showed strong positive associations between food safety risk perception and adhering to recommended food safety practices. Interventions that simply state basic food safety principles may not be sufficient to improve food safety practices.…”
Section: Discussionmentioning
confidence: 55%
“…15 Other research has shown that certain subgroups within the older adult population engage in practices that can lead to foodborne illness in the home. Cates et al found that older men exhibited more risky behaviors than older women, as did older adults with higher education and higher incomes.…”
mentioning
confidence: 99%
“…Home economics courses in which food safety was traditionally taught are increasingly rare or optional in school systems around the United States (15,64). As a result, a large proportion of adults have limited food preparation experience, have never learned basic food safety principles, and thus, may lack the knowledge needed to keep themselves and their families safe (7,10,37,39,51,57,60,63). Clearly, opportunities to learn how to practice safe food handling are needed.…”
mentioning
confidence: 99%